Fructose-Based Production of Short-Chain-Length and Medium-Chain-Length Polyhydroxyalkanoate Copolymer by Arctic Pseudomonas sp. B14-6 - Tae-Rim Choi; Ye-Lim Park; Hun-Suk Song; Sun Mi Lee; Sol Lee Park; Hye Soo Lee; Hyun-Joong Kim; Shashi Kant Bhatia; Ranjit Gurav; Kwon-Young Choi; Yoo Kyung Lee; Yung-Hun Yang (Polymers, 2021)
Arctic bacteria employ various mechanisms to survive harsh conditions, one of which is to accumulate carbon and energy inside the cell in the form of polyhydroxyalkanoate (PHA). Whole-genome sequencing of a new Arctic soil bacterium Pseudomonas sp. B14-6 revealed two PHA-production-related gene clusters containing four PHA synthase genes (phaC). Pseudomonas sp. B14-6 produced poly(6% 3-hydroxybutyrate-co-94% 3-hydroxyalkanoate) from various carbon sources, containing short-chain-length PHA (scl-PHA) and medium-chain-length PHA (mcl-PHA) composed of various monomers analyzed by GC-MS, such as 3-hydroxybutyrate, 3-hydroxyhexanoate, 3-hydroxyoctanoate, 3-hydroxydecanoate, 3-hydroxydodecenoic acid, 3-hydroxydodecanoic acid, and 3-hydroxytetradecanoic acid. By optimizing the PHA production media, we achieved 34.6% PHA content using 5% fructose, and 23.7% PHA content using 5% fructose syrup. Differential scanning calorimetry of the scl-co-mcl PHA determined a glass transition temperature (Tg) of 15.3 °C, melting temperature of 112.8 °C, crystallization temperature of 86.8 °C, and 3.82% crystallinity. In addition, gel permeation chromatography revealed a number average molecular weight of 3.6 × 104, weight average molecular weight of 9.1 × 104, and polydispersity index value of 2.5. Overall, the novel Pseudomonas sp. B14-6 produced a polymer with high medium-chain-length content, low Tg, and low crystallinity, indicating its potential use in medical applications.